2007
DOI: 10.1373/clinchem.2006.076042
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and Estimates of Renal Function: Searching for a Better Measure of Kidney Function in Diabetic Patients

Abstract: ؊1 cut-points, diagnostic efficiencies of cystatin C (89% and 92%) were better than those of the other variables (79%-82% and 85%-86%, respectively; P ‫؍‬ 0.01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
11

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(126 citation statements)
references
References 40 publications
5
110
0
11
Order By: Relevance
“…RFD2, no renal function decline; RFD+, renal function decline; ACR, urinary albumin/creatinine ratio. the normal range (12)(13)(14), the use of these equations (15,16) in this study generally underestimated RFD prevalence compared with ascertainment by serial GFR (not shown).…”
Section: Discussionmentioning
confidence: 60%
“…RFD2, no renal function decline; RFD+, renal function decline; ACR, urinary albumin/creatinine ratio. the normal range (12)(13)(14), the use of these equations (15,16) in this study generally underestimated RFD prevalence compared with ascertainment by serial GFR (not shown).…”
Section: Discussionmentioning
confidence: 60%
“…Perlemoine et al did not find CysC to offer any advantage in detecting GFR -80 mL/min/1.73 m 2 , except in the sub-group of patients with a creatinine of less than 1 mg/dL (88 mmol/L) (96). Of these different studies, the study by Pucci et al which examined 288 diabetic patients (both types) with GFR measurement by plasma iohexol clearance and a wide range of GFR is undoubtedly one of the most important studies (162). The authors found a significantly better correlation between CysC and GFR than between creatinine and GFR.…”
Section: Diabetic Patientsmentioning
confidence: 99%
“…Ovaj parametar je pokazao dobru korelaciju sa metodama zlatnog standarda za određivanje JGF [1,4]. Cistatin C se do sada pokazao i kao osjetljiv parametar za procjenu početnog oštećenja bubrežne funkcije, što kod oboljelih od DM omogućava prevenciju i preduzimanje mjera u usporavanju ili zaustavljanju progresije hronične bubrežne bolesti i razvoju terminalne bubrežne insuficijencije [9,10].…”
Section: Uvodunclassified
“…Poznato je da se normalne vrijednosti kreatinina u serumu mogu održavati sve dok se bubrežna funkcija ne ošteti za polovinu od normalne. Pucci i saradnici [9] su u svom istraživanju pokazali prednost cistatina C, u odnosu na kreatinin, za procjenu početnog oštećenja bubrežne funkcije kod oboljelih od oba tipa DM. Cistatin C je u njihovom istraživanju bio povišen kada su vrijednosti JGF bile blizu referentnih vrijednosti (90ml/min/1,73m 2 ) ili u opsegu od 60 do 90 ml/min/1,73m 2 .…”
Section: Diskusijaunclassified
See 1 more Smart Citation